Stabilizing Indigo Z‐Isomer through Intramolecular Associations of Redox‐Active Appendages. Issue 46 (28th September 2021) - Broløs, Line; Klaue, Kristin; Bendix, Jesper; Grubert, Lutz; Hecht, Stefan; Nielsen, Mogens Brøndsted
Abstract: Photoswitchable small molecules, such as N, N' ‐disubstituted indigos, have received great interest within fields such as pharmacology, energy storage, and functional materials, as they represent key building blocks for reversible and non‐invasive control of chemical processes. However, to ensure applicability of photochromic systems it is of paramount importance to manipulate the photostationary state. In this work, we achieved this by tethering two redox‐active indenofluorene‐extended tetrathiafulvalene units to an N, N' ‐disubstituted indigo photoswitch. Upon two‐electron oxidation, we observe significantly enhanced stability of the Z ‐isomer, compared to the neutral compound, illustrated by a substantial increase in the half‐life from 0.48 seconds to 22 hours. This remarkable stabilization is ascribed to formation of strong, intramolecular π‐dimers between the oxidized subunits. Abstract : Redox‐active indenofluorene‐extended tetrathiafulvalene units were added as appendages to the indigo photoswitch. Upon oxidation of these two units to radical cations, a significantly enhanced stability of the indigo Z ‐isomer was observed. Thus, the half‐life for the Z ‐to‐ E isomerization changed from less than a second to several hours upon formation of the dication, ascribed to intramolecular association between the two radical cation units.